New perspectives in European innovation policy - Bastian Krieger; Georg Licht; Maikel Pellens (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2018)
Innovation is essential for economic growth, and governments must encourage firms to increase their investments in innovation. Europe is losing ground to its main Asian competitors when it comes to R&D investment, and is barely keeping pace with the U.S. Moreover, the rate of return on innovation has become significantly weaker in Europe. This has been caused by its relative lack of innovative SMEs, the slow diffusion of innovation, and the increasingly competitive innovation marketplace. In this light, scholars and policy makers are arguing for a new approach to European innovation policy that puts more weight on the development of disruptive innovation and on the diffusion of new technologies throughout the market.
Keywords: 330